The Effect of an Authentic Acute Physical Education Session of Dance on Elementary Students' Selective Attention. (5th February 2018) - Kulinna, P. H.; Stylianou, M.; Dyson, B.; Banville, D.; Dryden, C.; Colby, R.
Abstract : There have been calls to test the potential benefits of different forms of physical activity (PA) to executive function, particularly in authentic settings. Hence, the purpose of this study was to investigate the effect of an acute dance session within an existing physical education class on students' selective attention. The study employed a pre/posttest quasi-experimental design with a comparison group in one Aotearoa, New Zealand, primary school. Participants were 192 students (comparison group = 104 students) in Years 5 and 6. The intervention group participated in a dance-based physical education lesson while the comparison group continued their regular classroom work. PA during the physical education lesson was monitored using accelerometers. Selective attention was assessed at pretest and after the comparison/physical education sessions with the d2 Test of Attention. 2 × 2 ANOVA results suggested a significant time effect for all three measures, no significant group effects for any measures, and significant time by group interactions for TN and CP but not forE %. The intervention group improved significantly more than the comparison group for TN and CP. This study's findings suggest that existing school opportunities focused on cognitively engaging PA, such as dance, can improve aspects of students' selective attention.